The Dynamics of Constitutional Court Decisions on Open Proportional, Closed Proportional, And Limited Open Proportional Electoral Systems - Mulyadi, Dedi; Megawati, Leny (Yayasan Studi Cendekia Indonesia (YSCI), 2023)
This research discusses the electoral system as a way to regulate citizen participation in electing legislative and executive members. According to the Constitutional Court of the Republic of Indonesia's (MK-RI) decision on Law No. 7/2017 on Elections made on 15 June 2023, the open proportional electoral system will still be applied in 2024. Legal experts gave their opinions on open proportional, closed proportional, and limited proportional systems during the MK's decision-making process. This research uses a normative juridical method by identifying issues related to the background of the judicial review petition, alternative electoral systems, and judges' considerations of the Constitutional Court's decision on the electoral system. It is expected that the results of this research will show that the Constitutional Court's decision on the electoral system will show the advantages and disadvantages of open and closed proportional systems, which reflect the relationship between the democratic aspirations of the Indonesian people and other democratic aspirations.